Trace elements increase replicability of microbial growth - Amit Shimoga Nadig; Rotem Gross; Tobias Bollenbach; Gerrit Ansmann (Open Biology)
Trace elements are often omitted from chemically defined growth media. From established properties of trace elements, we deduce that this omission makes experiments unnecessarily sensitive to unavoidable contamination with trace elements. We confirm this experimentally by growing 11 bacterial strains in high replicate with and without supplementing trace elements, keeping all other conditions as fixed as possible to isolate the effect of trace elements. We find that supplementing trace elements considerably reduces variability of growth even in this benign scenario, and we argue that typical experimental set-ups exacerbate this. We discuss implications for the design and use of trace-element supplements and in particular argue that their use should be standard practice, as they can reduce variability of almost all experiments using chemically defined media, taking a step towards greater precision and replicability in microbiology.